Surfactant Content Influence On Formation Water Compatibility - Oktavia, Della Azlia; Ramadhan , Romal; Prabowo , Dimas Hadi; Syaifurrohman, Alfatih; Abdurrahman , Muslim (Newinera Publisher, 2024)
In the pursuit of resolving surfactant non-solubility issues for enhanced oil recovery, this study identifies surfactants that are soluble and compatible with the formation brine of the Langgak field. Over the course of 21 days, the solubility and compatibility of 12 various surfactants were evaluated in synthetic brine with a salinity of 100 ppm and a reservoir temperature of 58˚C. The results indicated that surfactants S3 to S11 were compatible, exhibiting no signs of cloudiness or precipitation, thus making them suitable for further testing. These surfactants are recommended to proceed to phase behavior and interfacial tension (IFT) tests to evaluate their performance and impact on brine formation under reservoir conditions. Conversely, surfactants S1, S2, and S12 demonstrated incompatibility with the Langgak field's brine, as evidenced by cloudiness and precipitation. This incompatibility highlighted specific surfactant compositions that do not align well with the brine composition, providing crucial insights for future surfactant formulation. Understanding these interactions aids in improving the process of choosing surfactants that work well in comparable conditions. Overall, this study establishes a foundational understanding of surfactant-brine interactions, guiding the selection of suitable surfactants for enhanced oil recovery in the Langgak field.